Lumberjanes. 2, Friendship to the max - Stevenson, Noelle; Stevenson, Noelle; Ellis, Grace; Watters, Shannon (Lumberjanes., 2015)
The Lumberjane girls at Miss Quinzella Thiskwin Penniquiqul Thisle Crumpet's Camp for Hardcore Lady-Types are not your average girls. After they learn to make friendship bracelets, they'll brush up on monsters and magic and take on some raptors. But it's the mysterious force wreaking havoc on the camp that will be their biggest challenge because it's not just a threat to their friends but could threaten the whole world.